Models of the lipovans’ integration into the multi-ethnic environment of bukovyna: from preservation of ethno-cultural identity to non-ethnic and globalization impacts - Ivan Vorotniak (Науковий вісник Чернівецького національного університету імені Юрія Федьковича. Історія, 2022)
The article under study highlights the process of resettlement and adaptation of Old Believers in the multi-ethnic environment of Bukovyna in the late 18th – early 20th centuries. The representatives of the Austrian administration of the region were active supporters of involving the Lipovans, motivating their perspective for Vienna officials by the fact that the new settlers, owing to their hard work and practical farming skills, will be able to influence positively the economic development of Bukovyna.